RP-HPLC Method for Simultaneous Estimation of Domperidone in Combination with Rabeprazole Sodium in Solid Dosage Form - V. Gawande, Vidya; P. Puranik, Manisha (Asian Journal of Chemistry, 2010)
The present work describes a reverse phase high performance liquid chromatographic method for simultaneous estimation of domperidone in combination with rabeprazole sodium in capsule formulation. Chromatography was performed on a Inertsil C18 (250 mm × 4.6 mm i.d.) column in isocratic mode with mobile phase containing 0.05 M potassium dihydrogen phosphate:acetonitrile:methanol in the ratio (40:30:30 % v/v/v) and pH of the final mobile phase was adjusted to 7.44 ± 0.03 with 5 M KOH. The flow rate was 1.0 mL/min and the eluent was monitored at 287 nm. The selected chromatographic conditions were found to effectively separate domperidone (run time 9.74 ± 0.33 min), rabeprazole sodium (run time 6.85 ± 0.46 min). Linearity for domperidone and rabeprazole sodium was found in the range of 3-300 and 2-200 μg/mL, respectively. The proposed method was found to be accurate, precise, reproducible and specific and can be used for simultaneous analysis of these drugs in capsule formulation.